Complete mitochondrial genome of the deep pugnose ponyfish Secutor ruconius (Perciformes: Leiognathidae) in the East China Sea. Issue 2 (3rd July 2019) - Sui, Yanming; Qin, Bo; Song, Xuefeng; Sheng, Wenquan; Zhang, Bianbian
Abstract: The complete mitochondrial genome sequence of Secutor ruconius is firstly described in this article. The total length of mitogenome is16, 465 bp. It contains 13 protein-coding genes, 22 tRNA genes, and 2 ribosomal RNA genes. The overall base composition of H-strand is 31.58% A, 28.65% C, 25.23% T, and 14.53% G, with an A + T bias of 56.81%. The phylogenetic analysis result showed that the S. ruconius, Zebrasoma flavescens, and Pristipomoides multidens were closely related.